Heart or mind - Jones, Patrick, 1961- (Unbarred., 2016)
In this remake of Shakespeare's Romeo and Juliet, long standing tension between African American and Somali students at Northeast High School in Minneapolis makes love difficult between Rodney, who is on probation, and Jawahir.